Ibu Kota Negara (IKN) dan Mitigasi Ancaman Terorisme: Pendekatan Kesejahteraan untuk Pencegahan Aksi Kejahatan di Indonesia - Annisa Yudha Apriliasari; Sapto Priyanto (LPPM Universitas Ekasakti Padang, 2024)
The relocation of the National Capital (Ibu Kota Negara/IKN) to East Kalimantan Province has sparked pros and cons regarding potential threats and ways of countering terrorism in the new capital city, called Nusantara. This paper aims to provide a design and framework for mitigating the threat of terrorism in the nation's capital city by using a welfare criminology approach. This paper uses a qualitative approach regarding secondary data sourced from statistical data publications, online media news, journal articles, and previous similar research/studies. The new IKN with the name Nusantara which carries the concept of a